Implementasi Teknik Motion Graphic pada Editing Video Animasi “Produk Aman, Kulit Nyaman” - Vanessa Valencia Eleora; Silvi Alin Dhiya; Encang Saepudin; Rinda Aunillah Sirait (Pusat Riset dan Inovasi Nasional, 2025)
The spread of illegal cosmetics in Indonesia remains a concerning issue, particularly through digital platforms. One of the main contributing factors is the lack of public awareness and understanding regarding the differences between legal and illegal products. To address this challenge, animation-based media was chosen as an effective educational tool. This paper describes the implementation of motion graphic techniques in producing the animated video “Produk Aman, Kulit Nyaman”, which emphasizes the importance of using safe and legally approved skincare products. Motion graphics were selected for their ability to dynamically present visual elements, making the message more accessible to the audience. The editing process is divided into three key stages: material collection, assembly, and testing. Material collection focuses on systematic asset organization; assembly involves animating the assets using Adobe After Effects based on a structured storyline; and testing includes internal evaluation and informal validation by five female high school students as representatives of the target audience. This approach shows that motion graphics are not only effective in conveying educational messages but also contribute creatively to improving consumer literacy.